Agro-industrial waste composites as components for rural buildings - Cravo, J. C.M. [UNESP]; Sartori, D. L. [UNESP]; Fiorelli, J. (Elsevier, 2017)
The growing demand of the consumer market for wood does not follow the same pace as its offer, demanding from the productive sector a search for alternative lignocellulosic raw materials, such as agro-industrial waste. Thus, this work presents two case studies that describe the production process and thermophysical and mechanical properties of particleboard manufactured with cement bags and coated with long-life packaging and sugarcane bagasse particleboard bonded with a castor oil-based bicomponent polyurethane resin. The performance evaluation of these materials, when applied as a ceiling in prototype poultry houses and as a lateral closure in a beef cattle management center, is also evaluated. For the thermophysical-mechanical characterization, specific recommendations in specific normative documents for this type of material were used and also methodologies to quantify the efficiency of the material for the performance evaluation in each of the applications. The results indicated that this waste evaluated has potential for particleboard production, since the thermophysical-mechanical properties qualify these materials for applications such as ceilings and as a structural component. The cement-bag particleboard coated with long-life packaging, when evaluated as a ceiling material in prototype poultry houses, provided a more comfortable environment for broiler breeding, significantly reducing the IAPfc; the sugarcane bagasse particleboard, when associated with wooden beams and applied to a cattle management center, presented structural performance consistent with the use requirements.
Keywords: Castor oil polyurethane adhesive; Cattle handling facilities; Ceiling in rural building; Cement bag; Particleboards; Sugarcane bagasse